2020
DOI: 10.5398/tasj.2020.43.2.151
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbial Population and Growth in Broiler Fed Organic Acids and Palm Fat-Composed Diet

Abstract: Organic acids (OA) are natural constituents of plant and animal tissues and their uses as feed additives are now being studied worldwide. Organic acids consisted of different acids and mixtures of several acids have an antimicrobial function and promote the growth performance of animals. The current experiment was designed to study the inhibitory activity of the organic acids, palm fat (PF), a combination of organic acids-palm fat (OAPF) against various pathogens and investigate the performance in dietary incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
0
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
2
0
0
2
Order By: Relevance
“…The decreased fecal N τ -MH excretion can be correlated with the improved amino acids digestibility such as arginine until phenylalanine in P2, but only arginine, lysine, and methionine significantly increased in P3 (Table 2). The present study was consistent with the result of Goh et al (2020), who reported that dietary inclusion of the mixture of organic acid-palm fat improved nutrient digestibility and had a beneficial effect on the growth performances of broiler chicken. An interesting result found in this research that BWG was not affected by the reduced feed consumption (Table 3) because it was covered by the increased protein and amino acid digestibility (Table 2).…”
Section: Immune Status and Growth Performancesupporting
confidence: 93%
“…The decreased fecal N τ -MH excretion can be correlated with the improved amino acids digestibility such as arginine until phenylalanine in P2, but only arginine, lysine, and methionine significantly increased in P3 (Table 2). The present study was consistent with the result of Goh et al (2020), who reported that dietary inclusion of the mixture of organic acid-palm fat improved nutrient digestibility and had a beneficial effect on the growth performances of broiler chicken. An interesting result found in this research that BWG was not affected by the reduced feed consumption (Table 3) because it was covered by the increased protein and amino acid digestibility (Table 2).…”
Section: Immune Status and Growth Performancesupporting
confidence: 93%
“…Feeding either MP-DTE or MP-La diets improved growth performances supported by higher body resistance and defense, as indicated by higher circulating levels of GSH-Px and SOD. The present results were consistent with the previous study that nutrient digestibility was beneficial for the improvement of growth performances in a broiler-given diet with an organic acid-palm fat mixture (Goh et al, 2020). A result that would be important in the present study was that feed consumption was not affected by any treatment, but BWG increased by the feeding effect of either dahlia inulin or L. acidophilus.…”
Section: Meat Quality and Growth Performancesupporting
confidence: 93%
“…Postbiotic yang disekresikan oleh bakteri asam laktat (BAL) dapat berupa asam laktat, asam propionate, asam butirat, bakteriosin, enzim, senyawa antioksidan dan berbagai senyawa metabolit lainnya (Thanh et al, 2009;Manin, 2010;Thu et al, 2011;Loh et al, 2014;Chuah et al, 2019;Yang et al, 2020). Postbiotik dilaporkan dapat berperan sebagai natural biopreservatives (Jama andVaradaraj 1999, Hidayatulloh et al, 2019), dan antibiotic growth promoters baik pada ayam petelur, maupun ayam pedaging (Thanh et al, 2009;Loh et al, 2014;Goh et al, 2020).…”
Section: Pendahuluanunclassified
“…Bakteri asam laktat dilaporkan dapat menghasilkan postbiotic berupa asam-asam organic, enzim ataupun bakteriosin dilaporkan dapat memperbaiki sistem pencernaan dan penyerapan nutrient serta menyeimbangkan populasi bakteri di dalam saluran pencernaan (Thu et al, 2011;Goh et al, 2020) sehingga dapat memperbaiki performan ayam broiler. Postbiotik yang dihasilkan oleh BAL dapat digunakan untuk menggantikan antibiotic growth promoters serta telah terbukti dapat meningkatkan produktivitas dan kesehatan saluran pencernaan ayam petelur dan ayam pedaging (Thanh et al, 2009;Loh et al, 2014;Goh et al., 2020).…”
Section: Materi Dan Metodeunclassified